Behavior of railroad bearing due to temperature and load using LISA FEA - Aco Wahyudi Efendi; Akbar Zulkarnain; Dadang Sanjaya Atmaja (Journal of Railway Transportation and Technology, 2022)
A very important element of railway is the rail bearing, different types of rail bearings that we know in Indonesia are wooden rail bearings, concrete rail bearings. In this study, the stress behavior that occurs in the two types of railway bearings due to the load and the occurring temperature effect is to be checked. It was found that the stress occurring in bearings with different materials, namely concrete and wood, when the The nominal stress can be seen on the concrete bearing is 11.87 N/mm2, on the wooden material the bearing load is 10.41 N/mm2. As for the temperature effect, it looks similar to the temperature of 80 °C for each material, but it can be seen that the temperature effect spreads from the surface due to the friction between the railroad tracks and the railroad wheels.